Structured mesh generation from doppler ultrasound images - Rui Chaves (2012)
Non-invasive ultrasound imaging of human arteries is a widely form used for medical diagnosis of arterial diseases, like atherosclerosis. The objective of this paper is to present a methodology for patient-specific construction of a structured mesh of the carotid artery bifurcation from images obtained with Doppler ultrasound techniques.